Hydrogen Peroxide Treatment of Softwood-Derived Poly(Ethylene Glycol)-Modified Glycol Lignin at Room Temperature - Thi Thi Nge; Yuki Tobimatsu; Shiho Takahashi; Toshiaki Umezawa; Tatsuhiko Yamada (Molecules, 2023)
Recently, a large-scale production system of softwood-derived poly(ethylene glycol) (PEG)-modified glycol lignin (GL) was developed to produce high-quality lignin derivatives with substantially controlled chemical structures and attractive thermal properties. In this study, the further upgrading of GL properties with carboxy functionalization was demonstrated through the room-temperature hydrogen peroxide (H2O2) treatment with the mass ratio of H2O2 to GL, 1:1 and 1:3, for 7 d. The changes in the chemical structure, carboxy group content, molecular weight, and thermal properties of the insoluble portions of partially oxidized glycol lignins (OGLs) were then investigated. Nuclear magnetic resonance and thioacidolysis data revealed that the oxidative functionalization involved the cleavage of β–O–4 linkages and the oxidative cleavage of guaiacyl aromatic rings into muconic acid-type structures. This was validated by attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy and potentiometric titration. Overall, the results suggested that the varying outcomes of carboxy group content (0.81–2.04 mmol/g OGL) after 7-d treatment depended on the type of the GL origin having varying amounts of the retained native lignin structure (e.g., β–O–4 linkages), which were prepared from different source-wood-meal sizes and PEG molecular masses.